Evaluation of filamentous heterocystous cyanobacteria for integrated pig-farm biogas slurry treatment and bioenergy production. (February 2020) - Lu, Yuzhen; Zhuo, Chen; Li, Yongjun; Li, Huashou; Yang, Mengying; Xu, Danni; He, Hongzhi
Highlights: Three filamentous cyanobacteria strains were selected based on viability in digestate. The pollutants remove ability from biogas slurry of pig farm was evaluated. The biochemical composition of algal biomass was examined. The biodiesel and theoretical biomethane potential of algal biomass were evaluated. The strain J is the best strain for biogas slurry treat and bioenergy production. Abstract: The study evaluates 36 filamentous heterocystous cyanobacteria for the treatment of biogas slurry from pig farm and the accumulation of biomass for bioenergy production. The results showed that only the strains B, J, and L were able to adapt to a 10% biogas slurry. The removal rates of ammonia nitrogen, total nitrogen, and total phosphorus for strains J and L were 92.46%–97.97%, 73.79%–79.90%, and 97.14%–98.46%, respectively, higher than that of strain B. Strain J had the highest biomass productivity and lipid productivity. Based on the biodiesel prediction results, it was concluded that strains J and L are more suitable for biodiesel production. The estimation of theoretical methane potential suggests that the algal biomass of strain J also have the desirable possibility of biogas generation. In summary, algal strain J ( Nostoc sp.) offers great potential for biogas slurry treatment and for the production of bioenergy.